Requirements Engineering - Hull, Elizabeth; Jackson, Ken; Dick, Jeremy (Springer London : Imprint: Springer, 2005)
This second edition follows quickly on the ?rst edition and is an indication of how fast the subject is changing and developing. In the past two years there have been signi?cant advances and these are re?ected in this new edition. Essentially, this is an update that places more emphasis on modelling by describing a greater range of approaches to system modelling. It introduces the UML2, which is the recent standard approved by the OMG. There is also an enhanced discussion on the relationship between requirements management and modelling, which relates well to the concept of rich traceability. The chapter on the requirements management tool DOORS has been revised to use Version 7 of the tool and this is complemented with examples taken from the DOORS/Analyst tool which demonstrates how the concepts of modelling can be captured and created within DOORS. The text is still aimed at students and practitioners of systems engineering who are keen to gain knowledge of using requirements engineering for system development. As before, a web site supporting additional material is available at: http://www.requirementsengineering.info Elizabeth Hull Ken Jackson Jeremy Dick June 2004 vii Preface to the First Edition Requirements Engineering is common sense, but it is perceived to be dif?cult and is not well understood. For these reasons it is generally not very well done.